2006
DOI: 10.1086/505768
|View full text |Cite
|
Sign up to set email alerts
|

On Adaptive Accuracy and Precision in Natural Populations

Abstract: Adaptation is usually conceived as the fit of a population mean to a fitness optimum. Natural selection, however, does not act only to optimize the population mean. Rather, selection normally acts on the fitness of individual organisms in the population. Furthermore, individual genotypes do not produce invariant phenotypes, and their fitness depends on how precisely they are able to realize their target phenotypes. For these reasons we suggest that it is better to conceptualize adaptation as accuracy rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 87 publications
5
45
0
Order By: Relevance
“…The various definitions of adaptation and maladaptation can be wearisome in their diversity, contradiction, and controversy (Williams 1966;Gould and Lewontin 1979;Rose and Lauder 1996;Crespi 2000;Nesse 2005;Hansen et al 2006). I therefore simply outline my own view, which experience suggests is shared by at least some other evolutionary ecologists.…”
Section: Hendry's Panglossian Paradisementioning
confidence: 99%
See 1 more Smart Citation
“…The various definitions of adaptation and maladaptation can be wearisome in their diversity, contradiction, and controversy (Williams 1966;Gould and Lewontin 1979;Rose and Lauder 1996;Crespi 2000;Nesse 2005;Hansen et al 2006). I therefore simply outline my own view, which experience suggests is shared by at least some other evolutionary ecologists.…”
Section: Hendry's Panglossian Paradisementioning
confidence: 99%
“…I will variously invoke both response variables in the following sections. Of additional interest, although not considered here, is the spread of individual phenotypes around an optimum (Hansen et al 2006), and the extent to which that variation might or might not be adaptive.…”
Section: Hendry's Panglossian Paradisementioning
confidence: 99%
“…At the level of the population, there are at least three components, which are additive (Armbruster et al 2004, 2009 a ; Hansen et al 2006; Pélabon et al 2012): (i) optimality of the mean, which is how far the mean of events departs from the optimum (=‘maladaptive bias’), (ii) the variance, which is how much individuals vary from the mean (=‘adaptive imprecision’), and (iii) the variance in the optimum. By extrapolation from measurement theory (Armbruster et al 2004; Pélabon et al 2012), these three components sum to the adaptive inaccuracy as \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$$\eqalign{{\rm adaptive}\,{\rm inaccuracy} = ({{\rm trait}\,{\rm mean}{\rm \ - }{\rm \ optimum}\,{\rm value}} )^{\rm 2} \cr {\rm + trait}\ {\rm variance + optimum}\,{\rm variance}}$$\end{document} …”
Section: Floral Specialization Fitness Trade-offs and Adaptive Accuracymentioning
confidence: 99%
“…On average, albeit only small for each bone, the degree of DA was higher for forelimbs (≈0.15% of trait size) compared to hindlimbs (≈0.05% of trait size) (Table 3). Coefficients of phenotypic variation were high, ranging from ∼300 to ∼1000%, reflecting small average DA and a very imprecise expression (Hansen et al 2006 [29]). Pairwise comparisons of forelimb vs. hindlimb elements, corrected for multiple testing, showed that DA was higher in forelimbs ( P<0.01 for all comparisons).…”
Section: Resultsmentioning
confidence: 99%